EFEKTIVITAS MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR KIMIA SISWA SMA NEGERI 16 BANDA ACEH - Ainun Mardhiah; Said Ali Akbar (UIN AR-RANIRY, 2018)
The observations result of the students of SMA Negeri 16 Banda Aceh, showing that the student were less motivated in learning process, they prefer to play and engrossed by their own activities, there were only several students whose really enthusiastic about the material being studied. In order of learning in the classroom went well, so that needs to be innovated the learning activities by using. One of the innovations was used, namely the instructional media, while the learning media that used was the dominoes card and the crossword puzzles. This study aimed to see the effectiveness of learning media on student learning outcomes in learning chemistry by using Dominoes card and crossword puzzle media. This research was the experimental, the research of this research was the student of XI-1 class student experiment class I (dominoes card media) and class XI-2 as experiment class II (crossword puzzle), with total sample was about 37 students. The sample selection based on Purpossive Sampling technique. The instruments used in the form of written tests consist of 20 multiple choice questions with cognitive competence level C1 (knowledge), C2 (understanding), and C3 (application), group worksheet (LKK) in the form of card media and a crossword puzzle, and implementation plan learning (RPP). The data collection techniques were by pretest and posttest, and then analyzed were by using the normality test, homogeneity test, and T test on hypothesis test with 19-version version of the Statistical Program for Social Science (SPSS) program. The results showed that there was no significant difference to the learning outcomes of students who were taught using domino card media and TTS media. It can be concluded that the domino card media and TTS media are very effective in improving the learning outcomes of the students of SMA Negeri 16 Banda Aceh.